Assistive technologies that support social interaction in long-term care homes: a scoping review. Issue 10 (15th October 2021) - Macdonald, Marilyn; Yu, Ziwa; Weeks, Lori E.; Moody, Elaine; Wilson, Beth; Almukhaini, Salma; Martin-Misener, Ruth; Sim, Meaghan; Jefferies, Keisha; Iduye, Damilola; Neeb, David; McKibbon, Shelley
ABSTRACT: Objective: The objective of this review was to chart the literature on assistive technologies (excluding robots) that support social interaction of older adults in long-term care homes, and to advance a definition of socially assistive technologies. Introduction: Loneliness and social isolation have adverse effects on the health and well-being of older adults. Many long-term care homes provide recreational programming intended to entertain or distract residents, yet the evidence of their effectiveness is limited. Absent from the literature are comprehensive reviews of assistive technologies (other than robots) that are used to support social interaction in long-term care homes. Inclusion criteria: The review considered research studies as well as gray literature that included older adults (≥65 years) living in long-term care homes. The concept of interest was the use of assistive technologies (excluding robots) that support social interaction in long-term care homes. Methods: The databases were searched on June 26, 2019, and included CINAHL Full Text (EBSCO), MEDLINE (Ovid), PsycINFO (EBSCO), Sociological Abstracts (ProQuest), Embase (Elsevier), and Web of Science (Clarivate). The search for gray literature was conducted in ProQuest Dissertations and Theses Databases and across 11 websites during September and October 2019. The recommended JBI approach to study selection, data extraction, and data synthesis was used. Results: Twenty-five articles were included in this review, with comparable numbers of quantitative (n = 6), qualitative (n = 9), and mixed methods (n = 7) studies, with the remaining articles employing non-empirical designs (n = 3). Technologies were categorized as low (easily recognizable to everyone), medium (more electronics), or high (involves internet). Two studies reported on low-assistive technologies, including videotapes and the telephone. Medium-assistive technologies were identified in nine studies and included videophones; Nintendo Wii; tablet-based games; picture- and video-viewing tools; and CRDL (pronounced "cradle"), a special instrument that translates touch into sound. More than half (n = 14) of the included articles utilized high-assistive technologies, such as computer labs/kiosks, tablet-based applications, social media (eg, Facebook), videoconferencing, and multi-functional systems. Five studies measured whether assistive technologies had an impact on the quantity of long-term care residents' social interaction levels. Qualitative themes were related to residents' social connections and experiences after using various technologies. Four studies systematically incorporated a framework/model, and Social Structuration Theory was considered the most comprehensive. In the absence of a definition of socially assistive technologies, the definition advanced from this review is as follows: Socially assistive technologies are user-appropriate devices and tools that enable real-time connectivity to enhance social interaction. Conclusions: Included literature reported the benefits of technology use, with considerable variability in engagement and no cost estimates. We recommend that future research continue to advance our definition of socially assistive technologies, make promising assistive technologies available in long-term care homes after studies are completed, report the costs of assistive technologies, and include participants with dementia and culturally and linguistically diverse backgrounds.